Layer-by-layer nanocoating of chlorophene-loaded polymeric micelles on silicone catheters - Chayanon Ngambenjawong (2018)
A nanostructured layer-by-layer (LBL) dip coating method for silicone catheters was developed and optimized for prolonged release of chlorophene to help prevent urinary tract infections often complicated from extended use of catheters. The coating technique comprised alternating layers of drug-loaded poly(ethylene glycol)-block-poly(E-caprolactone) (PEG-b-PCL) micelles and poly(acrylic acid) (PAA) held together by hydrogen bonding interaction. The sustained release kinetics of chlorophene from the coated catheter surface was achieved by crosslinking PAA with ethylenediamine. The coating and crosslinking were confirmed by ATR-FTIR spectroscopy. In addition, the polymeric micelles were also fluorescently labeled in order to quantify their release by spectrofluorometry method. FTIR spectra of the coated catheters showed strong carbonyl absorption of both PCL (1736 cm -1 ) and PAA (1708 cm -1 ) while the crosslinked ones revealed additional amide I (1643 cm -1 ) and amide II (1548 cm -1 ) absorption bands which confirmed successful crosslinking of the PAA layers. Comparing to the non-crosslinked catheters, the crosslinked ones displayed a more sustained release of micelles over 30 days. Such release behavior is more favorable for the extended prevention against bacterial infection associated with the clinical use of catheters.